Protective Effects of Cassia fistula Linn. On Reproductive Organs Weight and Tissue Biochemical Markers in Streptozotocin-Induced Diabetic Male Rats - Jangir, Ram Niwas; Jain, Gyan Chand; Jain, Aditya (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: This study aims to evaluate the impact of hydroethanolic extract from Cassia fistula pods on reproductive organs weight and biochemical markers within reproductive tissues in experimental diabetic rats. Materials and Methods: Type 1 diabetes mellitus was induced in male Wistar rats by administering a single intraperitoneal injection of streptozotocin. Diabetic rats were then given oral doses of Cassia fistula Pods Extract (CFPE) at 100, 250, and 500 mg/kg BW per day over a period of 60 days. The findings were compared to diabetic rats treated with the standard antidiabetic drug, glibenclamide (5 mg/kg). Measurements included relative weights of the testes, epididymis, vasa deferens, seminal vesicles, and ventral prostate. Additionally, levels of protein, glycogen, cholesterol, sialic acid, acid and alkaline phosphatases in the testes and epididymis, along with fructose content in the seminal vesicles, were analyzed. Results: The administration of varying doses of Cassia fistula Pod Extract (CFPE) in diabetic rats resulted in a dose-dependent improvement in the relative weights of the testes, epididymis, vasa deferens, seminal vesicles, and ventral prostate. Additionally, CFPE treatment restored the concentrations of protein, glycogen, cholesterol, sialic acid, acid phosphatases, and alkaline phosphatases in the testes and epididymis, compared to the diabetic control group. These findings were comparable with reference drug. Conclusion: The results of this study indicate that CFPE effectively improved the reproductive organ weights and restore the tissue biochemical parameters in diabetic male rats.
Keywords: Cassia fistula; Glibenclamide; Reproductive organs weight; Streptozotocin; Tissue biochemistry.